LANGUAGE LABORATORY MANAGEMENT: AN OBSERVATORY REVIEW - Wulida Makhtuna (BASIS (Bahasa dan Sastra Inggris), 2020)
Language laboratory facilitates the lecturers and the students in the process of learning a foreign language. However most of the language laboratories in Banjarmasin were not managed well. It can be seen that most of the laboratories were not managed well. This condition made the students not motivated to visit them. This study investigated the aspects of management and maintenance of the language laboratory in UIN Antasari Banjarmasin. It analyzed the organization of the English language laboratory, how it was managed by the laboratorians, and how it was maintaned. The method of the study was descriptive qualitative. The result of the study revealed that the management of the language laboratory was managed well but it needed some improvement in some facilities.